Impulse radiation of antenna with circular aperture in near zone - Думін, О. М.; Ахмедов, Р. Д.; Черкасов, Д. В. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 2018)
The field of circular aperture of uniformly distributed current is investigated by a time domain technique in near zone. Arbitrary time dependence of the given source was taken into account by numerical evaluation of Duhamel integral on transient response of the emitter. Gaussian’s function and its first order derivative were considered as time dependence of the current to approach the model of the shape of real signals. Distribution of energy density of impulse electromagnetic filed in Fresnel zone was build and analyzed.